Colombia : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2000)
Economic performance of Colombia deteriorated in 1998 and the recession has deepened further. The weak economic activity helped to lower the inflation and to narrow the external current account deficit. The fiscal position and the health of the financial sector continued to deteriorate. The government announced a medium-term economic reform program that requires an immediate floating of the exchange rate, strong fiscal adjustment, financial sector restructuring, and an accelerated structural reform program. The paper presents statistical data on the economic indices of Colombia.